2017
DOI: 10.7554/elife.21697
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Dnmt3a and Dnmt3b does not affect epidermal homeostasis but promotes squamous transformation through PPAR-γ

Abstract: The DNA methyltransferase Dnmt3a suppresses tumorigenesis in models of leukemia and lung cancer. Conversely, deregulation of Dnmt3b is thought to generally promote tumorigenesis. However, the role of Dnmt3a and Dnmt3b in many types of cancer remains undefined. Here, we show that Dnmt3a and Dnmt3b are dispensable for homeostasis of the murine epidermis. However, loss of Dnmt3a-but not Dnmt3b-increases the number of carcinogen-induced squamous tumors, without affecting tumor progression. Only upon combined delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 71 publications
3
39
0
Order By: Relevance
“…MEIS1/2, PBX1, HOXB1, SOX4) and 3AKO ectoderm (SOX11, SOX9, ZIC2, POU4F1, PAX7). DNMT3A is often mutated in human tumors (Kim et al, 2013), has been shown to act as a first hit mutation (Shlush et al, 2014), and its loss in hematopoietic stem cells and the epidermis promotes leukemia and squamous cell carcinoma formation, respectively (Rinaldi et al, 2017;Yang et al, 2016). It will be interesting in the future to further explore the possible role of increased transcriptional variability in tumor initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…MEIS1/2, PBX1, HOXB1, SOX4) and 3AKO ectoderm (SOX11, SOX9, ZIC2, POU4F1, PAX7). DNMT3A is often mutated in human tumors (Kim et al, 2013), has been shown to act as a first hit mutation (Shlush et al, 2014), and its loss in hematopoietic stem cells and the epidermis promotes leukemia and squamous cell carcinoma formation, respectively (Rinaldi et al, 2017;Yang et al, 2016). It will be interesting in the future to further explore the possible role of increased transcriptional variability in tumor initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, depletion of DNMT3A and DNMT3B was observed to impair human EpSC self-renewal and, in the case of DNMT3A, also affect differentiation in experiments performed both in vitro and with reconstituted epithelia in nude mice (Rinaldi et al, 2016). On the other hand, conditional deletion of Dnmt3a, Dnmt3b, or both in the epidermis of adult mice did not produce any obvious defect (Rinaldi et al, 2017). Mechanistically, de novo DNMTs have been found to associate with and promote the activity of enhancers controlling key genes for EpSC self-renewal and differentiation (Rinaldi et al, 2016).…”
Section: Dna Methylation In Normal Epidermal Homeostasismentioning
confidence: 95%
“…391,392 However, combined expression of Dnmt3a and Dnmt3b inhibits PPARγ expression by direct methylation of its promoter in squamous carcinomas. 393 PPARs are also closely related to the metabolism of CSCs. PPARα and PPARβ/δ regulate metabolic reprogramming in glioblastoma stem cells, lung CSCs, and mouse mammary gland cancer.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%